PENINGKATAN MENULIS ESAI TENAGA PENDIDIK UNTUK SELEKSI CALON GURU PENGGERAK (CGP) MENGGUNAKAN MODEL COOPERATIVE INTEGRATED READING AND CONVERSATIONS (CIRC) BERBASIS LIFE SKILLS - Fitri, Aidi (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
The involvement of educators in the selection of Prospective Teacher Teachers (CGP) in the Junior Vocational Middle School 5 environment is very low. This is because educators' ability to write essays is very low. Therefore, appropriate learning techniques are needed to improve these skills. Therefore, the Cooperative Integrated Reading and Composite (CIRC) technique can be used as the right solution to improve these skills. The method used in this research is descriptive and qualitative in the form of classroom action research. The research was conducted at SMP Negeri 5 Vocational Youth and the research subjects were educators who taught at the school. This research process was carried out in three cycles: pre-cycle, cycle I, and cycle II. The results of the research are as follows: The pre-cycle learning completion level was 12.50%, the first cycle was 56.25%, and the second cycle was 81.25%. The essay writing proficiency score increased from pre-cycle to cycle 1 and reached the index in cycle 2. Referring to the results of this research, the Cooperative Integrated Reading and Composite (CIRC) technique was proven to improve educators' essay writing skills. This is also proven by the increase in the number of educators who have experienced an increase in class 10.